Realizing World Class Bureaucracy: The Role of Human Rights Principles in Denpasar Public Services - Mega Asmara Purwantini; I Nyoman Subanda (Bulletin of Community Engagement, 2026)
This study examines the implementation of human rights-based public services in Denpasar City as part of efforts to strengthen bureaucratic reform toward a world-class bureaucracy. Using a qualitative descriptive multi-site approach, the research focuses on several strategic service units, namely Wangaya Regional Hospital, South Denpasar Subdistrict Office, Sanur Kaja Village Office, Public Service Mall, Social Affairs Office, and the Legal and Organization Division of the Denpasar City Regional Secretariat. Data were collected through semi-structured in-depth interviews, non-participant observation, and document analysis involving service standards, performance reports, complaints data, and bureaucratic reform documents. The findings show that human rights principles in public services have been implemented through accessibility improvements, priority services for vulnerable groups, complaint mechanisms, and digital-based service innovations. However, the implementation is still constrained by institutional resistance, limited resources, uneven staff capacity, weak coordination, and varying levels of public participation, especially among vulnerable groups such as the elderly and persons with disabilities. The study concludes that human rights-based public services in Denpasar have developed positively, but still require stronger inter-agency synchronization, more inclusive participation mechanisms, and continuous capacity building to achieve a truly responsive and equitable public service system.